A trend of surface solar radiation in Chiang Mai, Thailand - S. Promplin (2020)
© Published under licence by IOP Publishing Ltd. The solar radiation passing through the atmosphere to the earth surface has varied in both increasing and decreasing directions. The decreasing direction caused mainly by aerosols, which its properties can absorb and reflect solar radiation. The emission sources of aerosol are primarily from human activities. This study aims to delineate a trend of surface solar radiation in Chiang Mai by using data from 7 air quality monitoring stations, recording during 1995-2017 in urban and rural areas. According to the Mann Kendal Sen's Slope analysis, the results show that surface solar radiation in Chiang Mai has presented the decreasing trends in 5 stations which located in urban areas while the other 2 stations located in rural areas have presented increasing trends. This could be basically explained that the difference and intensity of activities between urban and rural areas has affected the variation of surface solar radiation.